2002
DOI: 10.1103/physrevb.66.144418
|View full text |Cite
|
Sign up to set email alerts
|

Effect ofA-site cation ordering on the magnetoelectric properties in[(LaMnO3)m/(

Abstract: In order to evaluate the effect of charge transfer and/or charge ordering in La 1Ϫx Sr x MnO 3 on the magnetic and transport properties, a library of ͓(LaMnO 3 ) m /(SrMnO 3 ) m ͔ n superlattices have been fabricated by the combinatorial pulsed laser deposition method. The properties of superlattices were found to depend strongly on the periodicity m; superlattices of mр4 behaved like a solid solution La 0.5 Sr 0.5 MnO 3 film, while the superlattices of mϾ4 were significantly different from the solid solution.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
93
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 115 publications
(97 citation statements)
references
References 28 publications
4
93
0
Order By: Relevance
“…Considering that both LMO and SMO films are antiferromagnetic insulators even under the epitaxial strain, 9,13 these data are consistent with our assumption that the orbital degree of freedom does play a crucial role at the interface of perovskite manganite. 16 Figure 4 shows proposed orbital structures at the LMO/SMO interfaces.…”
supporting
confidence: 79%
See 1 more Smart Citation
“…Considering that both LMO and SMO films are antiferromagnetic insulators even under the epitaxial strain, 9,13 these data are consistent with our assumption that the orbital degree of freedom does play a crucial role at the interface of perovskite manganite. 16 Figure 4 shows proposed orbital structures at the LMO/SMO interfaces.…”
supporting
confidence: 79%
“…This result is consistent with the previous studies on similar superlattices. 12,13 Interestingly, the substitution to the latticematched LSAT substrate significantly increases M. The overall feature of the ͓La3, Sr2͔ superlattice on LSAT becomes equivalent to the ferromagnetic LSMO ͑x = 0.4͒ film, as characterized by the large spontaneous M ͑ϳ3 B / Mn-site͒. The enhanced ferromagnetism is also observed in the ͓La6, Sr4͔ superlattice.…”
mentioning
confidence: 67%
“…The result is often the existence of interfacial transition layers with novel physical properties different from the bulk material ones. [3][4][5][6] The potential to design and control reconstructions of the different degrees of freedom (charge, spin, orbital, lattice) is a recognized strategy to tailor the electronic properties of these artificial materials.…”
Section: Abstract: Interface Engineering Manganites Nickelates Magmentioning
confidence: 99%
“…[10][11][12][13][14][15][16][17][18][19][20][21][22] In different all-manganite heterostructures, it has been observed that the properties of thin manganite layers may be modified with respect to their bulk behavior, for instance, by the appearance of a ferromagnetic moment in a nominally antiferromagnetic manganite 15,16,22 or by the formation of a ferromagnetic two dimensional electron gas at the interface between two antiferromagnetic insulating manganites. [10][11][12]14,[17][18][19][20] Orbital reconstruction, a modification of the orbital occupancy at interfaces between different materials, has also been observed.…”
Section: Introductionmentioning
confidence: 99%